2007
DOI: 10.1002/anie.200703399
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Edge‐Sharing BO4 Tetrahedra in the High‐Pressure Borate HP‐NiB2O4

Abstract: In the course of our structural investigations of borates synthesized under high-pressure, high-temperature conditions, we discovered several new high-pressure modifications [1][2][3][4][5] with interesting structural features and physical properties, for example, a new non-centrosymmetric modification of bismuth triborate (d-BiB 3 O 6 ).[6] Along with the investigation of these phase transitions, we aim to synthesize borates with new compositions, whose existence is presumably based on high-pressure condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 39 publications
5
70
0
Order By: Relevance
“…We add that the above mentioned high-pressure borate NiB2O4 shows similar optical features and is characterized as "light-green" [55]. Lines are guides to the eye.…”
Section: Samplesmentioning
confidence: 83%
See 1 more Smart Citation
“…We add that the above mentioned high-pressure borate NiB2O4 shows similar optical features and is characterized as "light-green" [55]. Lines are guides to the eye.…”
Section: Samplesmentioning
confidence: 83%
“…The nickel borate Ni3(BO3)2 is known for more than a century [13], whereas other borates, NiB2O4 and NiB4O7, were synthesized only recently, under high-pressure and high-temperature conditions [55,56]. For our studies, single crystals of Ni3(BO3)2 were grown by a gas-transport method in the evacuated quartz ampoules along with the nickel boracites single crystals [16].…”
Section: Samplesmentioning
confidence: 99%
“…15,16 The nickel borate compounds Ni 3 (BO 3 ) 2 and Ni(BO 2 ) 2 have been investigated as candidates for several applications based on this unique behavior. [17][18][19][20][21] Recently, Dincă et al reported that a nickel borate thin film electrodeposited from a dilute Ni 2+ solution in a borate electrolyte (a so-called Ni-B i thin film) functions as an efficient electrocatalyst in an oxygen evolution reaction. 22 The characteristics of these Ni-B i thin films were investigated by Ni Kedge X-ray absorption fine structure (XAFS) and electrochemical kinetics, and it was found that the average valence state of the nickel species changes from +2.0 to +3.6 in response to an applied positive voltage.…”
Section: Introductionmentioning
confidence: 99%
“…RE 4 B 6 O 15 (RE = Dy, Ho), [14][15][16] a-RE 2 B 4 O 9 (RE = Sm-Ho), [17][18][19] and the recently found HP-NiB 2 O 4 [20] show, besides new compositions, the new strucural motif of edge-sharing BO 4 -tetrahedra. HPNiB 2 O 4 is the first borate, in which every BO 4 -group shares one common edge with an adjacent BO 4 -tetrahedron.…”
Section: Introductionmentioning
confidence: 94%